La base cognitiva de una cultura tradicional - Sevilla Muñoz, Julia (Eslavística Complutense, 2007)
The definition of the cognitive base of the traditional culture is the main objective of this article in order to underline the importance of the formation of the joint cultural and linguistic competence for the foreign language adquisition. The working languages are the Spanish and the Ukrainian, our respective native languages.